Negotiation of meaning in task-based interaction among non-native learners of ESL - Nor'ain Hadhira Ayob (2011)
This case study investigated the negotiation of meaning among non-native learners of ESL in task-based interaction. The investigation was guided by two research questions: (1) how do learners negotiate for meaning in task-based interaction? (2) how does negotiation of meaning help learners in completing the task? This study was conducted among four students majoring in Teaching English_ as a Second Language (TESL) from a public higher learning institution in Kata Kinabalu, Sabah. The students' interaction during the task execution were recorded and later transcribed. The categories of negotiating moves were based on Long's Interaction Hypothesis (1980). The transcripts of students' interaction were then used to guide stimulated recall sessions and one focus group interview session. The findings of this study suggest that learners do negotiate for meaning in task-based interaction. However, learners' intentions vary greatly from the functions often associated with particular negotiating moves. The functions of negotiating moves found in this study can be categorized into three major categories; (i) addressing input incomprehensibility, (ii) responding emotively to previous utterance and (iii) encouraging each other to interact. It was also found that negotiation of meaning is helpful in completing the task since it helps learners to resolve communication breakdown and misunderstanding; and to achieve mutual decision. Nevertheless, negotiation of meaning is considered optional since learners were found to be able to successfully complete tasks even when negotiation was considered unsuccessful. Learners attributed this to two factors; (i) group's social dynamics and (ii) perception of task's priority. The insights gained from this study suggest that although negotiation of meaning is necessary for task completion, it is not definitive of task completion.